Manajemen Supervisi Kepala Sekolah Dalam Meningkatkan Kompetensi Guru Agama Islam Di SMA Negeri 1 Muaradua Kisam - Yusmaniar, (UNISAN JURNAL, 2024)
This research aims to explore the role of principal supervision in improving the competency of Islamic teachers at SMA Negeri 1 Muaradua Kisam. The research method used is qualitative with a case study approach. Data was collected through in-depth interviews with school principals, Islamic teachers, and direct observations at school. The research results show that school principal supervision plays an important role in improving the competence of Islamic teachers. Principals use a variety of supervision strategies, including classroom observations, reflective discussions, and advanced training, to help teachers improve the quality of their teaching. Apart from that, the principal also provides moral support and motivation to Islamic teachers to continue to develop themselves. Research findings also reveal that open and collaborative communication between school principals and Islamic teachers is very supportive in improving teacher competency. The results of this research have important implications for educational management practices in schools. School principals need to pay attention to their supervisory role in improving the competence of Islamic teachers, by ensuring that the strategies used are appropriate to the needs and context of the school. In addition, collaboration and good communication between school principals and Islamic teachers need to be improved to create a conducive learning environment and support teacher professional growth.